Isolation of proteins associated with kinetoplast DNA networks in vivo. - Xu, C (1993)
Kinetoplast DNA (kDNA), the mitochondrial DNA of trypanosomes, is a highly condensed disc-shaped network of catenated DNA circles consisting of maxicircles, the equivalent of conventional mitochondrial DNA, and several thousand smaller circular DNAs termed minicircles. Upon cell lysis, kDNA expands, giving rise to a two-dimensional network of catenated circles with an overall diameter close to that of the whole cell. To identify proteins associated with the condensed form of kDNA in the cell, proteins were reversibly crosslinked to kDNA in whole cells of Crithidia fasciculata by formaldehyde treatment. Crosslinked networks were purified and found to retain a condensed structure which becomes fully expanded upon proteinase K treatment or reversal of the crosslinks by heating at 65 degrees C. Five low molecular weight proteins released from the kDNA by heat treatment were purified by polyacrylamide gel electrophoresis and their amino-terminal sequences were determined. PCR amplification and sequence analysis of cDNA sequences between these amino-terminal sequences and the miniexon (spliced leader) sequence present at the 5' end of all C. fasciculata mRNAs predicts the presence of 9-amino acid presequences with features characteristic of mitochondrial presequences on three of the proteins. Two of these proteins are lysine-rich basic proteins. These findings suggest that basic proteins may play a role in the condensation of kDNA in the kinetoplast and that these proteins are imported into the kinetoplast by a mechanism involving a cleavable presequence.